2023
DOI: 10.1021/jacs.3c11449
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonds of Halogen(I) Ions─Where Are We and Where to Go?

Lianne H. E. Wieske,
Mate Erdelyi

Abstract: Halenium ions, X + , are particularly strong halogen-bond donors that interact with two Lewis bases simultaneously to form linear [D•••X•••D] + -type halonium complexes. Their three-center, four-electron halogen bond is both fundamentally interesting and technologically valuable as it tames the reactivity of halogen(I) ions, opening up new horizons in a variety of fields including synthetic organic and supramolecular chemistry. Understanding this bonding situation enables the development of improved halogen(I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 130 publications
0
1
0
Order By: Relevance
“…Halogen bonding has been a significant addition to crystal engineers tool-kit and utilized to design materials with novel properties, including thermally expanding, soft and room temperature phosphorescent crystals. 151 Several halogen-bonded emissive co-crystals have been reported and fine-tuning of their emission has been realised through crystal engineering interventions. However, in the majority of systems, the interaction is used as an additional hook to associate the crystal components or acts as a competing associative force during crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…Halogen bonding has been a significant addition to crystal engineers tool-kit and utilized to design materials with novel properties, including thermally expanding, soft and room temperature phosphorescent crystals. 151 Several halogen-bonded emissive co-crystals have been reported and fine-tuning of their emission has been realised through crystal engineering interventions. However, in the majority of systems, the interaction is used as an additional hook to associate the crystal components or acts as a competing associative force during crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors have suggested that crystallographic analysis can reveal close contacts, but calculated electrostatic potentials can provide insight into the extent of variations in positive potentials on the cationic surfaces and negative potentials on the anionic surfaces. Similarly, Wieske and Erdelyi [147] discussed the bonding features of hypervalent halogen (I) complexes. They argued that the halonium ions bound to two carbons, [C-X-C] + , do not possess halogen-bond donor character, as discussed by many research groups in the past.…”
Section: Evidence Of π-Hole Halogen Bonds Formed By Halogen Derivativ...mentioning
confidence: 99%